Membrane Application in the Recovery of Gaharu Active Marker Compound from Water Mixture - Chin Weng, Foo (2013)
This study focuses the membrane application in the recovery of gaharu active marker compound from water mixture. The objective of this study is to design the separator process using membrane technique to recover gaharu active marker compound from water mixture and to analyse the recovered gaharu marker compound using membrane separation. The gaharu marker compounds that needed to be separated are agarospirol, jinkohol, α-guainene and selina-3,11-dien-9-al. Preparative High Performance Liquid Chromatography was used as the qualitative analysis of the gaharu active marker compound in the mixture. The membrane was applied to separate the marker compound from the water mixture. Milipore Stirred Ultrafiltration Cell Model 8200 was used as the membrane separation proces unit. Field Emission Scanning Electron Microscopy was used to capture microscope image of the TS40 and SB90 nanofiltration membrane used in the experiment. At the end of the experiment, TS40 nanofiltration membrane was able to separate the gaharu marker compounds at the average flux value of 0.45 ml/cm2.h to 2.00 ml/cm2.h with varying pressure from 1 bar to 4 bar.